2020
DOI: 10.3390/ijerph17124297
|View full text |Cite
|
Sign up to set email alerts
|

Role of Area-Level Access to Primary Care on the Geographic Variation of Cardiometabolic Risk Factor Distribution: A Multilevel Analysis of the Adult Residents in the Illawarra—Shoalhaven Region of NSW, Australia

Abstract: Background: Access to primary care is important for the identification, control and management of cardiometabolic risk factors (CMRFs). This study investigated whether differences in geographic access to primary care explained area-level variation in CMRFs. Methods: Multilevel logistic regression models were used to derive the association between area-level access to primary care and seven discrete CMRFs after adjusting for individual and area-level co-variates. Two-step floating catchment area method was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…The patterns were consistent across the six CMRFs analysed in this study; and comparable with similar studies reported nationally and globally. Based on our findings, we recommend further area-level research to discern the role of other contextual factors not analysed in this study especially the area-level access to health care services to determine its existing role and adequacy 78 , and evidence based universal interventions for the prevention and control of CMRFs but proportionate to the priority level of the populations based on area-level disadvantage. www.nature.com/scientificreports/ www.nature.com/scientificreports/ www.nature.com/scientificreports/ www.nature.com/scientificreports/ www.nature.com/scientificreports/…”
Section: Resultsmentioning
confidence: 88%
“…The patterns were consistent across the six CMRFs analysed in this study; and comparable with similar studies reported nationally and globally. Based on our findings, we recommend further area-level research to discern the role of other contextual factors not analysed in this study especially the area-level access to health care services to determine its existing role and adequacy 78 , and evidence based universal interventions for the prevention and control of CMRFs but proportionate to the priority level of the populations based on area-level disadvantage. www.nature.com/scientificreports/ www.nature.com/scientificreports/ www.nature.com/scientificreports/ www.nature.com/scientificreports/ www.nature.com/scientificreports/…”
Section: Resultsmentioning
confidence: 88%
“…Sixteen articles, published between 2003 to 2021, focused on accessibility to general practice (GP) services [ 16 , 33 , 43 , 56 , 73 , 75 79 , 81 , 84 , 91 , 93 , 100 , 102 ]. Of those articles, three were from the same study [ 75 , 76 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Articles focused on specific target populations, including antenatal [ 33 ], > 65 years [ 100 ], patients with chronic disease [ 73 ], and rural, regional, or remote [ 75 , 76 , 78 , 79 , 84 , 93 , 100 ]. Ten articles accounted for SES status using the ABS SEIFA [ 56 , 75 , 76 , 79 ], with six articles further specifying the index used, including the Index of Relative Socio-economic Advantage and Disadvantage (IRSAD) [ 91 ] and IRSD [ 16 , 33 , 43 , 73 , 102 ]. Seven articles used standardised geographic classification systems to define remoteness areas, including ARIA [ 81 ], ABS ASGC-RA [ 91 ], and ABS ASGS-RA [ 16 , 43 , 73 , 77 , 100 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation